2015
DOI: 10.1080/01635581.2016.1115097
|View full text |Cite
|
Sign up to set email alerts
|

Fish oil supplementation during chemotherapy increases posterior time to tumor progression in colorectal cancer

Abstract: The authors evaluated clinical outcomes during and after chemotherapy in colorectal cancer patients supplemented with fish oil during the first 9 wk of treatment. Thirty individuals never submitted to chemotherapy were randomized into supplemented group (SG), which received 2 g/day of fish oil (0.6 g/day of EPA and DHA) for 9 wk or control group (CG), which received neither fish oil nor placebo. Outcomes assessed were number of chemotherapy cycles administered; days undergoing chemotherapy; number of delays an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 17 publications
1
22
0
3
Order By: Relevance
“…The current study extends these findings and suggests that, in patients with established MSI tumors, high intake of MO3PUFA after diagnosis may also be beneficial and contributes to improved survival. Several clinical trials have indicated that MO3PUFA supplementation reduces circulating and colonic mucosal levels of pro‐inflammatory mediators, including prostaglandin E 2 and chemokine C‐C motif ligand 2, improves immune response, and delay tumor progression . These findings support our results and may have important clinical implications.…”
Section: Discussionsupporting
confidence: 88%
“…The current study extends these findings and suggests that, in patients with established MSI tumors, high intake of MO3PUFA after diagnosis may also be beneficial and contributes to improved survival. Several clinical trials have indicated that MO3PUFA supplementation reduces circulating and colonic mucosal levels of pro‐inflammatory mediators, including prostaglandin E 2 and chemokine C‐C motif ligand 2, improves immune response, and delay tumor progression . These findings support our results and may have important clinical implications.…”
Section: Discussionsupporting
confidence: 88%
“…In addition, fish oil supplementation enhances the effects of chemotherapy in colorectal cancer [32, 33]. The main component of fish oil consists of ω-3 polyunsaturated fatty acids (PUFAs) such as DHA and EPA.…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, some clinical trials demonstrated that EPA and DHA supplementation during chemotherapeutic treatments improved CRP values, CRP/albumin status, and positively modulated the nutritional status of CRC patients (77, 78). Likewise, evaluation of clinical outcomes during and after chemotherapy in CRC patients supplemented with fish oil containing EPA and DHA during the first 9 weeks of treatment unraveled that the time to tumor progression was significantly longer in the supplemented with respect to the control group (79). Interestingly, a recent phase II double-blind randomized, placebo-controlled trial of EPA administration to advanced CRC patients undergoing liver resection surgery demonstrated that EPA is incorporated into secondary CRC tissue and has systemic anti-inflammatory activity.…”
Section: ω3 Pufa As Potential Adjuvants In the Therapy Of Crcmentioning
confidence: 99%